Analyzing The Effect of “Lantana Amara” Invasion on Density, Frequency, Dominance, And Important Value Index of Woody Species in The Lake Tana Sub Basin - Bayu Tesfaye; Soeprobowati Tri Retnaningsih; Adissu Solomon; Warsito Budi (E3S Web of Conferences, 2023)
Invasive plant species can disrupt recovery pathways by altering species interactions and ecosystem structure and functioning. The species compositional changes induced by Lantana invasion are primarily driven by gradual changes in species density. This research tries to analyze the effect of Lantana camara invasion of density, dominance, important value index, species richness, and evenness in the Lake Tana subbasin. The finding revealed that species dominance (48.36) in the not invaded area is higher than invaded area (121.07). The total number of species recode in invaded (2031) area was lower than in the uninvaded area (5085). The uninvaded area (3.73) is richer in terms of species composition than invaded area (2.84). The invasive species Lantana camara affects the density, frequency, and important value index of other species by suppressing their composition. It also affects the species distribution by affecting species evenness and richness of the study area. The invasive species affect biodiversity composition and ecosystem services in the Lake Tana sub-basin. Comprehensive management strategies should be designed by the government, policymakers, and environmentalists to minimize the effect of Lantana camara invasion on biodiversity composition.